Basic and clinical studies on cefluprenam in respiratory infection - Yamasaki, Tohru; Ichimiya, Tomoku; Nasu, Masaru; Kitagawa, Kazuo; Fujii, Hiromichi; Tashiro, Takayoshi; Goto, Yoichirou; Nagai, Hiroyuki; Hirai, Kazuhiro; Hiramatsu, Kazufumi; Tokimatsu, Issei; Kawano, Hiroshi; et al. (Japanese Journal of Chemotherapy, 1995)
We conducted a basic and clinical studies of cefluprenam (CFLP), a new parenteral cephem antibiotic for injection, with the following results. 1. Antibacterial activity: The minimum growth inhibitory concentrations (MIC) of CFLP against 329 strains of 6 species isolated from clinical materials were measured by the criteria of the Japanese Society of Chemotherapy. Reference drugs were ceftazidime (CAZ), cefuzonam (CZON), flomoxef (FMOX) and imipenem/cilastatin (IPM/CS). CFLP showed potent antibacterial activity, as CZON and FMOX did, against Staphylococcus aureus, Streptococcus pneumoniae and Moraxella catarrhalis. CFLP was the most active among the reference drugs against Escherichia coli and Klebsiella pneumoniae. 2. Serum and sputum levels of CFLP: CFLP (1 g intravenous drip infusion for 60 minutes) were mesured in a patient with acute bronchitis Peak serum level was 66.0μg/ml at the end of drip infusion, and peak sputum level was 2.38μg/ml at 4-5 hour after infusion. 3. Clinical study: CFLP wan administered 11 patients with respiratory infections at 2g/day b.i.d.for 6-14 days. The clinical efficacy was rated as excellent in 1, good in 5, fair in 2 and poor in 1 patient. No adverse reaction nor abnormal laboratory findings were noted.